The Effect of Speed, Agility, Quickness Exercises on Developing some Skill Abilities and Physical in Youth Handball Player (Texas Journal of Medical Science, 2022)
The study aims at:- Preparing exercises using (Speed, Agility, Quickness) method and its impact on developing somephysical fitness and skills abilities for youth handball players.- Identifying the effect of (Speed, Agility, Quickness) exercises in developing some physical fitnessabilities for youth handball players.It is hypothesized that:- There are statistically significant differences between the two groups (experimental and control) forthe pre and posttests in the development of some physical fitness and skill abilities for youthhandball players.- There are statistically significant differences between the two groups (experimental and control) forthe post-test in the development of some physical fitness and skill abilities for youth handballplayers.- The researchers have used the experimental method by designing the experimental and control groupswith pre and post tests for its suitability and the nature of the current research problem.- The research community is represented by the youth players of Salah El-Din Handball Club for thesports season 2020/2021 numbering to (22) players. A number of (4) players are excluded as follows(2) goalkeepers and (2) players, due to their participation in the pilot experiment. So, the number ofsample members is (18) players constituting (81.8%) of the research community.Conclusions:- The (Speed, Agility, Quickness) exercises have brought about a development in the studied fitnessvariables of quickness and agility.- The exercises used have led to a development in the level of the offensive side, especially the skill ofshooting, whether from the remote areas or those close to the goal.